Effects of Subchronic Copper Poisoning on Cecal Histology and Its Microflora in Chickens - Huang, Cheng; Shi, Yan; Zhou, Changming; Guo, Lianying; Liu, Guohui; Zhuang, Yu; Li, Guyue; Hu, Guoliang; Liu, Ping; Guo, Xiaoquan (Frontiers in Microbiology, 2021)
Copper (Cu) is an important trace element, which participates in the process of animal growth and development. But if excessive, it shows a high degree of toxicity to organisms. The purpose of this study was to determine the effects of oral copper sulfate (CuSO4,350ppm) on growth performance, cecal morphology and its microflora of chickens(n=60) after 30, 60 and 90 days. The results showed that after 90 days of copper exposure, the body weight decreased, the cecal mucosa fell off, and the vacuolation and inflammatory infiltration appeared at the bottom of the lamina propria. In addition, using 16S rDNA sequencing method, we observed that copper exposure changed the richness and diversity of intestinal microorganisms. At the phylum level, Proteobacteria and Actinobacteria both significantly increased while Bacteroidetes significantly decreased in the Cu group compared to CK group. At genus level, the relative abundance of Rikenellaceae_RC9_gut_group decreased significantly while the Ruminococcaceae_UCG-014, Lachnoclostridium and [Eubacterium]_coprostanoligenes_group increased significantly after copper exposure, and the change of microflora was most significant at 90 days. Moreover, the relevance of genus-level bacteria was altered. PICRUST analysis revealed potential metabolic changes associated with copper exposure, such as Staphylococcus aureus infection and metabolic disorders of nutrients. To sum up, these data show that subchronic copper exposure not only affects the growth and development of chickens, but also causes the imbalance of intestinal microflora, which may further induce metabolic disorders in chickens.